Pengaruh Brand Image, Harga, dan Kualitas Produk terhadap Keputusan Pembelian Konsumen di Marketplace - Mahkrani (Teewan Journal Solutions, 2025)
in online Marketplaces. As digital trading platforms become increasingly popular due to convenience and product variety, consumers' purchase decisions are influenced by multiple factors, including brand perception, price evaluation, and product quality. This research employs a quantitative approach with a survey method involving 120 active Marketplace users in Indonesia. Data were analyzed using multiple linear regression. The results indicate that brand image, price, and product quality simultaneously have a significant effect on purchase decisions. Partially, brand image and product quality have a positive and significant influence, while price shows a positive but not statistically significant effect. These findings suggest that in the digital Marketplace era, consumers tend to prioritize brand reputation and product quality over price alone. Therefore, online businesses should focus on strengthening brand positioning and maintaining high product quality to enhance consumer purchasing decisions.